Strategic talent management : contemporary issues in international context - Sparrow, Paul; Scullion, Hugh; Tarique, Ibraiz (Cambridge : Cambridge University Press, 2014)
With contributions from leading scholars and practitioners, this Cambridge Companion examines the topical issue of talent management from a strategic perspective, mapping out insights from a number of related fields including strategy, organisational learning, marketing and supply chain management. The authors examine the challenges faced when viewing talent management in a global context, showing how both comparative and international HRM thinking have become increasingly important when, for example, managing talent in emerging markets or trying to globalise the talent management function. The book concludes with a valuable summary of key learning points about talent management for both practitioners and researchers, as well as a discussion of the most fruitful areas for future research. This Companion will be an essential resource for academic researchers, graduate students and practitioners of global strategic talent management.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Personnel management; Employee motivation; Creative ability in busines